2019
DOI: 10.21203/rs.2.9862/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Internal limiting membrane insertion technique combined with nerve growth factor injection for large macular hole

Abstract: Background The study was proposed to determine whether the nerve growth factor (NGF) combined with an internal limiting membrane (ILM) insertion technique was effective in the large idiopathic full-thickness macular hole (iFTMH) surgery. Methods A subset of 18 eyes (July 2015-October 2017) diagnosed as a large iFTMH were enrolled in this study. The subjects were treated using ILM insertion technique alone (ILM group) or ILM combined with NGF injection (NGF group) and the follow-up period was 6 months. Macul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…However, it was still imprudent to conclude that both 2 surgical techniques performed equal effectiveness on MH over 650 μm for only 2 included studies (98 eyes) in the subgroup that reported the surgical outcomes. Since a large number of studies reported the prompt and efficient reconstruction of the super large MH treated with the filling technique [3,32], it is of great importance to conduct more comparative studies to explore the role of ILM flap filling technology in recovering giant neuroepithelial defects in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was still imprudent to conclude that both 2 surgical techniques performed equal effectiveness on MH over 650 μm for only 2 included studies (98 eyes) in the subgroup that reported the surgical outcomes. Since a large number of studies reported the prompt and efficient reconstruction of the super large MH treated with the filling technique [3,32], it is of great importance to conduct more comparative studies to explore the role of ILM flap filling technology in recovering giant neuroepithelial defects in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Other techniques that have been described in limited case reports or series include novel adjuvant agents such as mesenchymal stem cells [135] and intravitreal nerve growth factor [136], increasing perifoveal compliance by hydrodissection [137], and increasing the macular hole index (which has been correlated with better post operative BCVA) by tapping the edges of the MH, that have all reported excellent rates of anatomical closure. In addition, multiple recent techniques specific to addressing myopic macular holes in the presence of concurrent retinal detachments have been described, such as macular buckling [138], suprachoroidal buckling [139], and scleral imbrication [140], which are out of the scope of this review.…”
Section: Other Techniquesmentioning
confidence: 99%
“…Recently, some scholars have proposed that mNGF may promote the postoperative recovery of visual function of IMH. Research showed that PPV combined with ILM peeling and intravitreal injection of mNGF is a safe and effective treatment for large macular holes, which can not only improve the BCVA, but also promote functional recovery of External Limiting Membrane (ELM) and Ellipsoid Zone (EZ) [7] . With the ophthalmic imaging technology developed rapidly, OCTA has been widely used in ophthalmology due to the advantages of non-invasive, repeatable, safe, and convenient.…”
Section: Introductionmentioning
confidence: 99%